A combined framework for service identification and congestion management. - Jian Fu
Service identification and congestion management are important functions of the ISO in maintaining system security and reliability. Most approaches in the literature solve the problem sequentially, which may lead to an under or over-estimation of the service requirement and transaction curtailment. A few of them do it iteratively which is quite time consuming. In this paper, a combined framework for service identification and congestion management is proposed. The ideal objective function is to maximize the overall profit of all market participants. Practically, an upper bound cost minimization is suggested and has been applied to identify two of the services, the reactive support and real power loss services, in case of congestion. The service costs plus the congestion cost are minimized. Results show that the proposed approach results in a smaller transaction curtailment. The curtailment also depends on the relative cost of congestion with respect to the cost of services
Keywords: Bid price; Congestion cost; Congestion management; Ideal objective function; Lower bound profit; Overall profit maximisation; Power system reliability; Power system system security; Profit maximisation; Reactive support services; Real power loss services; Service cost; Service identification; Service requirement; Transaction curtailment; Upper bound cost minimization